National vs. non-national soccer referee: physiological, physical, and psychological characteristics - Castillo-Rodríguez, A.; Muñoz-Arjona, C.; Onetti-Onetti, W. (Research Quarterly for Exercise and Sport, 2022)
Purpose: The objectives of the present study were to analyze the relationship between psychological variables (self-esteem, anxiety and self-confidence) assessed before the competition and physical and physiological responses demonstrated during the competition in soccer referees and to compare these psychophysical and physiological responses by category (CAT; national and non-national).